2015
DOI: 10.1890/14-0490.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological strategies predict associations between aquatic and genetic connectivity for dryland amphibians

Abstract: The study of how population genetic structure is shaped by attributes of the environment is a central scientific pursuit in ecology and conservation. But limited resources may prohibit landscape genetics studies for many threatened species, particularly given the pace of current environmental change. Understanding the extent to which species' ecological strategies--their life histories, biology, and behavior-predict patterns and drivers of population connectivity is a critical step in evaluating the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 62 publications
4
54
0
Order By: Relevance
“…This is not only true of invertebrates, as Mims et al (2015) came to a similar conclusion about amphibians breeding in the study region. It is especially notable that intermittent and ephemeral reaches still host equivalent or greater numbers of total and unique species to their perennial counterparts, and it is important to note that these species still rely on networks of perennial and nonperennial stream segments in seasonal environments.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is not only true of invertebrates, as Mims et al (2015) came to a similar conclusion about amphibians breeding in the study region. It is especially notable that intermittent and ephemeral reaches still host equivalent or greater numbers of total and unique species to their perennial counterparts, and it is important to note that these species still rely on networks of perennial and nonperennial stream segments in seasonal environments.…”
Section: Discussionsupporting
confidence: 74%
“…This trend is likely to continue based on climate projections and increasing human water demand (Meixner et al, 2016;Serrat-Capdevila et al, 2007). Although perennial streams are undoubtedly important to many species, understanding the broader context of how communities vary among stream reaches of varying flow permanence within fragmented stream networks is essential to conserving them (Mims, Phillipsen, Lytle, Kirk, & Olden, 2015). Although perennial streams are undoubtedly important to many species, understanding the broader context of how communities vary among stream reaches of varying flow permanence within fragmented stream networks is essential to conserving them (Mims, Phillipsen, Lytle, Kirk, & Olden, 2015).…”
mentioning
confidence: 99%
“…Hence, the distance among regions, the small body size and the harsh conditions during the dry season may result in the highly significant population differentiation. Reproductive mode was shown to influence population structure in amphibians (Measey et al 2007;Fouquet et al 2015;Mims et al 2015;Paz et al 2015). Species showing reproduction independent of open water, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For montane amphibians topography, mainly elevation (Funk et al 2005;Kershenbaum et al 2014) and slope (Kershenbaum et al 2014;Mims et al 2015), or abiotic factors, mainly desiccation risk (Peterman et al 2014;Emel and Storfer 2015), were shown to have an important influence on population structure and connectivity. In accordance with these findings, our best model (1400 m asl elevation model) includes topography (elevation) and presumably desiccation risk.…”
Section: Discussionmentioning
confidence: 99%
“…A number of freshwater ponds and streams are ephemeral or intermittent, which alters connectivity and habitat size, with consequences for species with varying reliance on water (e.g., amphibians, invertebrates) [125,126]. For instance, severe drought extirpated top predators in desert streams in Arizona, USA, allowing mesopredators to increase through release from competition [83].…”
Section: Persistence Of Landscape Structurementioning
confidence: 99%